2019
DOI: 10.3892/or.2019.7386
|View full text |Cite
|
Sign up to set email alerts
|

Οlive tree blossom polyphenolic extracts exert antioxidant and antimutagenic activities in vitro and in various cell lines

Abstract: Olive oil has held a prominent place in the Mediterranean diet since ancient times due to its beneficial effects on human health thus, becoming the subject of great scientific interest. Although numerous studies have examined the biological action of olive and olive oil extracts, the literature lacks studies investigating the putative antioxidant capacity of olive tree flower extracts. Given that olive tree flowers are actually by-products of the olive oil production process with high waste burden for the envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
2
13
0
1
Order By: Relevance
“…The free-radical scavenging activity (RSC) of wine extracts was evaluated by a 2,2-Diphenyl-1-picrylhydrazyl (DPPH • ) radical assay [ 83 ], as previously described, with slight modifications [ 49 , 84 , 85 , 86 ]. Briefly, 900 μL of methanol and 50 μL of freshly prepared methanolic solution of DPPH • radical (2 mM) were mixed with 50 μL of each wine extract in different concentrations (ranging from 1.56 to 150 μg/mL).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The free-radical scavenging activity (RSC) of wine extracts was evaluated by a 2,2-Diphenyl-1-picrylhydrazyl (DPPH • ) radical assay [ 83 ], as previously described, with slight modifications [ 49 , 84 , 85 , 86 ]. Briefly, 900 μL of methanol and 50 μL of freshly prepared methanolic solution of DPPH • radical (2 mM) were mixed with 50 μL of each wine extract in different concentrations (ranging from 1.56 to 150 μg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…The assay of DNA relaxation from peroxyl radicals has already been described [ 49 , 85 , 94 , 95 , 96 ]. The plasmid (pBluescript SK+, Fermentas, Waltham, MA, USA) DNA normally exists in the supercoiled conformation but, following a single-strand break, it is converted to an open circular conformation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical composition of OMW has already been published from our research group (9). Indicatively, it was found to be rich in four polyphenols, namely hydroxytyrosol, tyrosol, caffeic acid, and pcoumaric acid, which are main constituents of olive oil (41,42).…”
Section: Methodsmentioning
confidence: 99%
“…The FC assay is not specific for particular groups of phenolic compounds but is used for the determination of their total concentration in various extracts (40,41). Typically, the TPC is determined via a gallic acid (GA) standard curve (42,43). Gao et al (44) suggested that the main polyphenolic component of each food extract may be used as the assay standard.…”
Section: In Vitro Cell-free System Measurementsmentioning
confidence: 99%